Precision measurements of linear scattering density using muon tomography. (12th July 2016) - Åström, E.; Bonomi, G.; Calliari, I.; Calvini, P.; Checchia, P.; Donzella, A.; Faraci, E.; Forsberg, F.; Gonella, F.; Hu, X.; Klinger, J.; Ökvist, L. Sundqvist; et al.
Abstract: We demonstrate that muon tomography can be used to precisely measure the properties of various materials. The materials which have been considered have been extracted from an experimental blast furnace, including carbon (coke) and iron oxides, for which measurements of the linear scattering density relative to the mass density have been performed with an absolute precision of 10%. We report the procedures that are used in order to obtain such precision, and a discussion is presented to address the expected performance of the technique when applied to heavier materials. The results we obtain do not depend on the specific type of material considered and therefore they can be extended to any application.